2014
DOI: 10.1111/joim.12258
|View full text |Cite
|
Sign up to set email alerts
|

Murine solid tumours as a novel model to study bacterial biofilm formation in vivo

Abstract: Bacteria of many species are able to invade and colonize solid tumours in mice. We have focused on Salmonella enterica serovar Typhimurium. Detailed analysis revealed that such tumour‐invading Salmonella form biofilms, thus providing a versatile in vivo test system for studying bacterial phenotypes and host–pathogen interactions. It appears that biofilm formation by S. typhimurium is induced as a defence against the immune system of the host, and in particular against neutrophils. Further, we extended our work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…It employs transplantable solid tumors in mice that are preferentially colonized by P. aeruginosa as well as by other bacteria after systemic administration (18). The microenvironment of the colonized tumor leads to biofilm formation by the bacteria (18)(19)(20). Apparently, this microenvironment of the murine tumor resembles very closely that found in the CF lung or in burn wounds (21).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It employs transplantable solid tumors in mice that are preferentially colonized by P. aeruginosa as well as by other bacteria after systemic administration (18). The microenvironment of the colonized tumor leads to biofilm formation by the bacteria (18)(19)(20). Apparently, this microenvironment of the murine tumor resembles very closely that found in the CF lung or in burn wounds (21).…”
mentioning
confidence: 98%
“…We have recently described a model that might accomplish the requirements. It employs transplantable solid tumors in mice that are preferentially colonized by P. aeruginosa as well as by other bacteria after systemic administration (18). The microenvironment of the colonized tumor leads to biofilm formation by the bacteria (18)(19)(20).…”
mentioning
confidence: 99%
“…As observed before for the facultative anaerobes (31) and P. aeruginosa (30,32), V. parvula accumulated in the tumor tissue. However, accumulation of V. parvula was only detected when sufficient numbers of bacteria were intravenously administered (2 ϫ 10 8 CFU).…”
Section: Resultsmentioning
confidence: 60%
“…It has previously been shown that facultative anaerobic bacteria, such as Salmonella Typhimurium and Escherichia coli, are able to colonize solid subcutaneous tumors of the colon carcinoma cell line CT26 in a mouse tumor model (50). We have further demonstrated that P. aeruginosa, although rapidly cleared from the blood and other organs, is also able to gather and multiply specifically in the murine tumor tissue following intravenous administration (31,32). Of note, whereas facultative anaerobic bacteria like Salmonella colonize the whole tumor tissue, including the anaerobic center, the nonfermenter P. aeruginosa colonized mainly the outer rim of the tumor tissue.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation